Essential Decision a Minimal Approach to Design - Chen, Xi; Ingsiriwat, Paijit; Marc Schafer, David (Journal of Contemporary Social Sciences and Humanities, 2025)
In a materially rich modern world, how does one apply the core minimalist concept that possessing and consuming less is actually more and use this as a guide to design products and change our lives? Minimalism is an art and design style that follows the maxim ‘less is more’ and has, in recent times, evolved and integrated into lifestyles. The author was curious how, in this age of material abundance, was it possible to possess a few items and how to choose items one needs. The author began with understanding the essence of minimalism by reading widely on this topic and following the works of luminary Japanese designers and a well-known Japanese housewife Maria Kondō and her approach to organizing possessions at home. The author then applied this understanding to her room to get a more in-depth insight into how these principles work in life. After that, a few participants were recruited for this study. They were required to send pictures of their desks and engage in a conversation via chatting apps to provide insights into how they organize their possessions. The author found that a modular system that is highly adaptable to suit multiple users and their needs to organize their possessions but still retaining the overall concept of minimalism does indeed help to improve their lives.